A comparative study of the level of emotional response and self- confidence among players and teams the first and last centers in Iraq Super League football - Al-Nasser , Abdul Rahman (Journal of Physical Education, 2010)
Plays a psychological factor played a key role in the preparation of a football player and stands at the forefront of psychological factors side of emotional being one of the psychological factors associated with achieving victory and sporting achievement as well as self-confidence, which raises many of the positive emotions among the players as the study aimed to identify the level of response to the emotional and the degree of self-confidence among players, teams centers, first and last in Iraq Super League in football season 2007-2008, as applied researcher standard response to emotional and self-confidence to the players, teams first centers are police and air force teams and centers the last justice and the torch has been researcher concluded from this study that there are significant differences between teams, first and last positions in most of the characteristics of emotional response as well as self-confidence